Structure and Transport of Atlantic Water North of Svalbard From Observations in Summer and Fall 2018 - Kolås, Eivind; Koenig, Zoé Charlotte; Fer, Ilker; Nilsen, Frank; Marnela, Marika (Journal of Geophysical Research: Oceans, 2020)
The transport of warm Atlantic Waters north of Svalbard is one of the major heat and salt sources to the Arctic Ocean. The circulation pathways and the associated heat transport influence the variability in the Arctic sea ice extent, the onset of freezing, and marine ecosystems. We present observations obtained from research cruises and an autonomous underwater glider mission in summer and fall 2018, to describe the hydrographic structure, volume transport, and circulation patterns of the warm Atlantic Water Boundary Current between 12°E and 24°E north of Svalbard. The Atlantic Water volume transport reaches a maximum of 3.0 ± 0.2 Sv in October, with an intraseasonal variability of 1 Sv (1 Sv = 106 m3 s−1). During summer and late fall, we observed an Atlantic Water recirculation flowing westward (0.1–0.2 Sv) in the outer part of the section away from the shelf break. This counter current appears to be a part of an anticyclonic circulation in the Sofia Deep. The strength of the Atlantic Water recirculation and the Atlantic Water boundary current is very sensitive to the wind stress curl: The boundary current volume transport doubled in less than a week, corresponding to a transition from strongly negative (−10−6 N m−3) to strongly positive (10−6 N m−3) wind stress curl over the Sofia Deep. A previously unknown, deep bottom‐intensified current is observed to flow parallel to the boundary current, between the 1,500 and 2,000 m isobaths. Historical data in the region support the presence of the bottom‐intensified current. publishedVersion